Ergonomic chair design for school computer laboratories in the Cape Metropole, Western Cape, South Africa - Van Niekerk, Sjan-Mari (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.